2016
DOI: 10.3109/13645706.2016.1151891
|View full text |Cite
|
Sign up to set email alerts
|

Open vs. closed reduction combined with minimally invasive plate osteosynthesis in humeral fractures

Abstract: Aim To explore a more effective surgical procedure, the outcomes of closed manipulative reduction (CMR) combined with minimally invasive plate osteosynthesis (MIPO) and conventional open reduction and internal fixation (ORIF) for treating proximal humeral fractures were compared. Material and methods In a retrospective study of patients operated for humerus shaft fractures from April 2008 to July 2011, the outcomes of 33 patients treated with CMR/MIPO were compared with the outcomes of 42 patients treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The MIPO technique using the relative stability principle in shaft fractures has gained popularity for its potential advantage in causing fewer soft-tissue complications. [8, 9, 39, 40] Open reduction and internal fixation through either an anterolateral or posterior approach needs significant soft-tissue and local vascularity disruption, which may lead to a decreased fracture healing potential and increase the incidence of iatrogenic radial nerve injury and deep infection. [33] This meta-analysis showed that the MIPO technique had a significantly lower incidence rate of iatrogenic radial nerve injury than ORPF.…”
Section: Discussionmentioning
confidence: 99%
“…The MIPO technique using the relative stability principle in shaft fractures has gained popularity for its potential advantage in causing fewer soft-tissue complications. [8, 9, 39, 40] Open reduction and internal fixation through either an anterolateral or posterior approach needs significant soft-tissue and local vascularity disruption, which may lead to a decreased fracture healing potential and increase the incidence of iatrogenic radial nerve injury and deep infection. [33] This meta-analysis showed that the MIPO technique had a significantly lower incidence rate of iatrogenic radial nerve injury than ORPF.…”
Section: Discussionmentioning
confidence: 99%
“…By reading the title and abstract, 355 papers were excluded according to the inclusion and exclusion criteria. A total of 42 studies were assessed by reading the full text; eventually, 16 studies involving 1050 patients (464 patients in the MIPO group and 586 patients in the ORIF group) were included in the meta-analysis [9,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The flow diagram of the included studies is shown in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%
“…were included in the meta-analysis [9,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The flow diagram of the included studies is shown in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%
“…The methodological quality of the RCTs [9,27] was assessed by the Cochrane Handbook, the assessment results are summarized in Figure 2. The quality index scores of the non-RCTs [10,[15][16][17][18][19][20][21][22][23][24][25][26]28] were 14-20. The assessment results are summarized in Table 2.…”
Section: Literature Searchmentioning
confidence: 99%